Maintaining the safety of our dams and reservoirs : proceedings of the 18th Biennial Conference of the British Dam Society at Queen's University, Belfast, from 3-6 September 2014 - Pepper, A. T. (ICE Publishing, 2014)
This text contains the proceedings of the 18th Biennial Conference of the British Dam Society, Maintaining the Safety of our Dams and Reservoirs. It covers a wide range of topics that are of direct relevance to all who work with dams and reservoirs, whether in the UK or abroad, be they owners, maintainers, designers or constructors.